Membangun Pedesaan Melalui Program Sinergi Pemberdayaan Masyarakat di Kecamatan Polokarto Kabupaten Sukoharjo - Siswadi, Dewi Ratna Nurhayati & (Joglo, 2009)
ABSTRACT The policy of National Development in Education, especially for University, is more capable done by doing education research and investigation in science and technology (IPTEK). It could give service to the society which useful and neded for support the development. Basides the policy is also guided to make an improvement of the revelance and quality of the service to society by implementing and spreading applied research, investigation and applied technology to use in a productive activity and to improve the quality of society living but also to give more experience to the university about the real problems faced by society. Such effort to rely government policy is by holding program sinergi Pemberdayaan Potensi Masyarakat (SIBERMAS), which involving some universities i.e. Slamet Riyadi University Surakarta, Veteran Pembangunan Nasional University Yogyakarta and Sukoharjo Local Government (PEKMKAB Sukoharjo). This implementation of SIBERMAS program is done on there village i.e. Polokarto Sukoharjo, Central Java, by involving lecturer staffs from any subjects according to skills needed students and technical teams from some Departements in its implementation. The methods used in SIBERMAS program is PACA (Participatory Appraisal Competitive Advantage) / (PRA (Participatory Rural Appraisal). The program is started with axploratory research that is to know all about the situation of location according to the people live there. To implement the priority program of the the firs year i.e. to socialize the empower program of the family productive economy the training and cultivating corn mango and non pesticide vegetables. The training about processing mango, natural solid liquid fertilizer, study about partnership transfer of technology and aids of applied technology tools. The training about production management and marketing to practive and evaluate the selling of natural fertilizer and non pesticide products. The result of society serice in SIBERMAS shows that there cooperation in solving the district/local problems and creating new trade opportunity based on the available potential between the universities and socientes in developing out nation through society empowering in creating entreneurship culture. Keyword : SIBERMAS District Real Income, Applied Technology.